2015
DOI: 10.1007/s00299-015-1794-9
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of transcription factor aflR in Aspergillus flavus confers reduction to aflatoxin accumulation in transgenic maize with alteration of host plant architecture

Abstract: We report success of host-induced gene silencing in downregulation of aflatoxin biosynthesis in Aspergillus flavus infecting maize transformed with a hairpin construct targeting transcription factor aflR. Infestation of crops by aflatoxin-producing fungi results in economic losses as well as negative human and animal health effects. Currently, the control strategies against aflatoxin accumulation are not effective to the small holder farming systems in Africa and this has led to widespread aflatoxin exposure e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…Previous research efforts to use RNAi to silence toxin production resulted in a mere 5- to 10-fold reduction and impaired the growth of transgenic plants, presumably because the RNAi cassette targeted a fungal transcription factor gene that may have had other silencing effects ( 23 ). Before embarking on this project, a bioinformatics analysis determined that the Aspergillus polyketide synthase gene does not have any notable DNA sequence homology with the maize genome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research efforts to use RNAi to silence toxin production resulted in a mere 5- to 10-fold reduction and impaired the growth of transgenic plants, presumably because the RNAi cassette targeted a fungal transcription factor gene that may have had other silencing effects ( 23 ). Before embarking on this project, a bioinformatics analysis determined that the Aspergillus polyketide synthase gene does not have any notable DNA sequence homology with the maize genome.…”
Section: Discussionmentioning
confidence: 99%
“…Research on plant-induced RNAi silencing of single fungal genes has shown reduction of aflatoxin levels in the range of 60 and 97% [17,23,38]. Masanga et al [23] demonstrated a 14-fold reduction in aflatoxin accumulation in transformed maize, expressing a hairpin construct targeting aflR.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up study on this prediction by a research group in Kenya led to the transformation of aflR hairpin constructs into a susceptible tropical maize line resulting in a significant (14-fold) reduction in aflatoxin levels. While these results were commendable, the transgenic maize had an altered plant phenotype possibly due to HIGS mistargeting by aflRsi RNAs [55]. Consequently, this study creates a platform from which the effects of silencing other aflatoxin biosynthetic genes on aflatoxin levels could be evaluated.…”
Section: Transgenic Approaches Towards Aspergillus Flavus and Aflmentioning
confidence: 96%